Computation Error Analysis in Digital Signal Processing Systems With Overscaled Supply Voltage - Yang Liu; Tong Zhang; Parhi, K.K. (IEEE transactions on very large scale integration (VLSI) systems, 2010)
It has been recently demonstrated that digital signal processing systems may possibly leverage unconventional voltage overscaling (VOS) to reduce energy consumption while maintaining satisfactory signal processing performance. Due to the computation-intensive nature of most signal processing algorithms, the energy saving potential largely depends on the behavior of computer arithmetic units in response to overscaled supply voltage. This paper shows that different hardware implementations of the same computer arithmetic function may respond to VOS very differently and result in different energy saving potentials. Therefore, the selection of appropriate computer arithmetic architecture is an important issue in voltage-overscaled signal processing system design. This paper presents an analytical method to estimate the statistics of computer arithmetic computation errors due to supply voltage overscaling. Compared with computation-intensive circuit simulations, this analytical approach can be several orders of magnitude faster and can achieve a reasonable accuracy. This approach can be used to choose the appropriate computer arithmetic architecture in voltage-overscaled signal processing systems. Finally, we carry out case studies on a coordinate rotation digital computer processor and a finite-impulse-response filter to further demonstrate the importance of choosing proper computer arithmetic implementations.